Model for assessing information logistics systems in banks: Lithuanian case study - Asta Valackiene; Rasa Andrijauskaite (Logistics, 2021)
This study aims to provide valuable insights into the information logistics process and to ensure the effectiveness of its systems in the business environment by discussing the banking sector. In this regard, this study investigates the information logistics system of a bank's IT service center. For this purpose, the instruments for transfer of the bank Z information logistics system were empirically tested in order to highlight the assessment factors; the various factors related to the bank Z information logistics management methodologies and the methods were examined. The key findings and contributions were achieved, i.e., we developed a systematic model for assessing information logistics systems in a bank. The model explains the adaptation of various methodologies and techniques of information logistics systems in the banking sector and justifies the platform of interaction of information logistics processes. The first part of the article introduces the concept of information logistics systems and unpacks its development and management methodologies and processes. The second part introduces the research methodology for assessing information logistics systems. The results highlight the system of management processes applied to the information logistics and discuss the areas and tools for improving this system. The main outcome of this research is presented in the third part, where the systematic model for assessing information logistics systems is developed. This model distinguishes the stages of information logistics cycles and the levels of the information logistics environments. It indicates the information logistics methodologies and techniques linking to the six types of management processes in the IT service center of a bank. The developed model helps to make the assessment of the information cycle more efficient and demonstrates a customizable result which can be adapted by other companies within their IT service centers.
Keywords: 650; information logistics system; assessment; management methods of process identification; model